Membangun Komunikasi Rumah Tangga dalam Pemilihan Metode Kontrasepsi di Desa Tunggulsari, Kecamatan Kaliori, Kabupaten Rembang, Jawa Tengah - Siti Musyarofatul Islamiyah; Desy Santi Rozakiyah (JSPH (Jurnal Sosiologi Pendidikan Humanis), 2025)
Communication between married couples in choosing a contraceptive method is an important part of the continuity of family planning programs. The selection of contraceptive methods involves the role of family planning field officers (PLKB), family planning cadres, and village midwives. The purpose of this study was to determine the communication process between husbands and wives in choosing contraceptive methods in Tunggulsari Village. This study used a qualitative method with a case study design. Data collection techniques included observation and semi-structured interviews conducted face-to-face, with informants selected using purposive sampling. Data analysis utilized Cresswell's data analysis technique, which involves transcribing interview results, reducing data, coding the reduced data, drawing conclusions, verifying data, and triangulating data. The results of the study indicate that communication between spouses in choosing contraceptive methods is quite good, although the participation of husbands is still low. Wives tend to play a more active role in decision-making because they are the primary users of contraceptives, considering personal comfort as well as fears and social stigma associated with long-term contraceptive methods (MKJP). Family planning counselors, family planning cadres, and village midwives play a role in education, counseling, and contraceptive method services. New findings indicate specific requirements for female sterilization services in Rembang District. This study emphasizes the importance of intensive education and local policy adjustments to increase acceptance of MKJP. Additionally, the level of husband participation needs to be further increased so that the use of contraceptive methods is not solely the responsibility of the wife.